Human Machine Interface (HMI) for Boiler Efficiency Calculation using Visual C# and OPC Server / ระบบ Human Machine Interface (HMI) สำหรับคำนวณประสิทธิภาพหม้อไอน้ำ โดยใช้ Visual C# และ OPC Server - Assawinchaichote / จิตพร เหล่าอิ่มจันทร์ และวุฒิชัย อัศวินชัยโชติ, Chittaporn Hlaoimchan and Wudhichai (Naresuan University Journal: Science and Technology (NUJST); Vol 24 No 2 (2016): May-August 2016, 2016)
บทคัดย่อ บทความนี้นำเสนอ การออกแบบระบบ Human Machine Interface (HMI) เพื่อคำนวณหาประสิทธิภาพของหม้อไอน้ำ โดยใช้ Programmable Logic Control (PLC) ควบคุมเและรับค่าจากเครื่องมือวัด ใช้ Visual C# เขียนโปรแกรมแสดงผล คำนวณ และติดต่อกับ PLC ผ่านทาง OPC Server ค่าจากเครื่องมือวัดที่รับเข้ามาที่เวลาเดียวกัน ถูกนำมาคำนวณหาประสิทธิภาพของหม้อไอน้ำ และแสดงผลแบบ Online ให้ผู้ปฎิบัติงานทราบทันที ทำให้ทราบสภาพปัจจุบันของหม้อไอน้ำ ง่ายต่อการวางแผนในการซ่อมบำรุง เพื่อให้หม้อไอน้ำทำงานได้อย่างมีประสิทธิภาพ ส่งผลให้ประหยัดค่าใช้จ่ายในด้านเชื้อเพลิง การทดลองรับส่งค่าระหว่าง HMI กับ PLC ผ่านทาง Port Ethernet ที่ Computer จะติดตั้งโปรแกรม OPC Server เพื่อสร้าง Tag ติดต่อกับ Address ของ PLC ใช้ Visual C# ที่ติดตั้ง Component COPC.DLL เขียนโปรแกรมรับส่งค่าจาก OPC Server นำค่า Digital/Analog input มาแสดงผลที่หน้าจอ และทดลองส่งค่าจาก HMI ออกไปที่ Digital/Analog output ของ PLC ส่วนการทดลองเพื่อคำนวณประสิทธิภาพของหม้อไอน้ำ ค่า Input จะถูกป้อนเข้าไปที่ OPC Server เพื่อส่งค่าให้กับ HMI โดยมี Input บางส่วนที่ต้องกำหนดเองตามประเภทของหม้อไอน้ำ จากนั้นจะนำมาคำนวณหาประสิทธิภาพ และแสดงผลที่หน้าจอ HMI เมื่อค่า Input เปลี่ยนแปลง ค่าประสิทธิภาพที่คำนวณได้จะเปลี่ยนแปลงไปด้วย ผลการทดลองพบว่า การเขียน HMI โดยใช้ Visual C# สามารถรับค่า Input เข้ามาคำนวณได้โดยไม่ต้องไปแก้ไขในโปรแกรม PLC ทำให้ไม่เปลืองหน่วยความจำของ PLC ค่า Input ที่นำมาคำนวณ เป็นค่าที่เวลาเดียวกัน ช่วยลดความผิดพลาดจากการให้ผู้ปฎิบัติงานเดินจดค่าจากเครื่องมือวัดซึ่งทำให้เวลาไม่ตรงกัน จากเดิมที่คำนวณประสิทธิภาพนานๆ ครั้ง งานวิจัยนี้ทำให้ทราบค่าประสิทธิภาพได้อย่างรวดเร็ว และลดความผิดพลาดจากการคำนวณโดยผู้ปฎิบัติงาน HMI ที่เขียนด้วย Visual C# สามารถนำข้อมูลไปใช้ในรูปแบบอื่นๆ ได้อีก เช่น เก็บค่าใว้ใน Database เพื่อดูข้อมูลย้อนหลัง หรือให้แสดงผลผ่านทาง Website   คำสำคัญ : หม้อไอน้ำ ประสิทธิภาพ เครื่องมือวัด    Abstract   This article presents a design of Human Machine Interface (HMI) for computing the boiler efficiency using PLC such that it can control and obtain the measured values from the measurement tools. The program, display and calculation are based on Visual C# while contacting with PLC was made through OPC Server so that several PLC could be simutaneously contacted. All measured values obtaining from the measurement tools at the same time were calculated to identify the boiler efficiency. The results were displayed online to inform operators. As a result, this could show the current condition of the boiler so it was easy for maintenance which could maximize the boiler efficiency and reduce fuel cost. To conduct a transmission test between HMI and PLC via port Ethernet, OPC Server is installed in a computer to create Tag connected to PLC Address. Visual C# installed in Component COPC.DLL writes a program that transmits the values from OPC Server and displays Digital/Analog input on screen. HMI is transmitted through PLC Digital/Analog output. To conduct a test of the boiler efficiency calculation, the input value is transmitted through OPC Server to transfer the values to HMI. Some input is identified according to types of boilers. After that the boiler efficiency is calculated and displayed on HMI screen. When Input values change, efficiency values change accordingly. The results show that using Visual C# to write HMI can receive Input value calculation without making any changes in PLC program. As a result, this can save PLC memory. Input values retrieved at the same time which is used for calculation can reduce errors caused by an operator who records values from measuring instrument. This study enables quick efficiency values and reduces calculating errors caused by an operator. HMI written by Visual C# can apply data in different formats. For instance, the values can be recorded in Database to enable retrieving previous information or to display the results via Website.   Keywords: HMI, Boiler, Visual C#, PLC
Keywords: หม้อไอน้ำ ประสิทธิภาพ เครื่องมือวัด HMI, Boiler, Visual C#, PLC